THE INFLUENCE OF FINANCIAL LITERACY, PERCEIVED BENEFITS, AND SOCIAL INFLUENCES ON INTEREST IN USE OF ILLEGAL FINTECH LENDING - Karina Lintang Ayu Salindri; Dyah Ratnawati (International Journal of Economy, Education and Entrepreneurship, 2023)
The increasing presence of fintech in social life reflects the annual changes in people's lifestyles, as the surrounding environment is predominantly occupied by information technology users who consider it a necessity for their daily lives. The objective of this study was to examine the influence of financial literacy, perceived benefits, and social influences on individuals' inclination to engage in illegal lending through fintech platforms. This research adopts a quantitative approach, with a sample size of 100 students from the Faculty of Economics and Business at UPN "Veteran" East Java. The data analysis technique employed in this study is Partial Least Squares (PLS). The findings indicate that social influence does not enhance the relationship between the interest in using illegal fintech platforms. However, both financial literacy and perceived usefulness demonstrate a positive impact on individuals' inclination to engage in illegal fintech lending